Symmetries, safety, and self-supervision - Dillon, Barry M.; Kasieczka, Gregor; Olischläger, Hans; Plehn, Tilman; Sorrenson, Peter; Vogel, Lorenz (SciPost physics, 2022)
Collider searches face the challenge of defining a representation of high-dimensional data such that physical symmetries are manifest, the discriminating features are retained, and the choice of representation is new-physics agnostic. We introduce JetCLR to solve the mapping from low-level data to optimized observables though self-supervised contrastive learning. As an example, we construct a data representation for top and QCD jets using a permutation-invariant transformer-encoder network and visualize its symmetry properties. We compare the JetCLR representation with alternative representations using linear classifier tests and find it to work quite well.